INFLUENCE OF MADRASAH PRINCIPALS' TRANSFORMATIONAL LEADERSHIP ON TEACHER PROFESSIONALISM IN THE DIGITAL ERA: A SEQUENTIAL EXPLANATORY MIXED-METHODS STUDY - Moch. Rikza Alkhubra Abdul Jabbar; Chusnul Chotimah; Mukhamad Sukur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the influence of transformational leadership exercised by madrasah principals on teacher professionalism and to explain the mechanisms underlying this relationship. A Sequential Explanatory Mixed Methods approach was employed. The quantitative phase involved 43 teachers selected through total sampling, while the qualitative phase included the madrasah principal, vice principals, teachers, administrative staff, and students selected using purposive and snowball sampling techniques. Quantitative data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), whereas qualitative data were analyzed following the interactive model of Miles, Huberman, and Saldaña. The integration of quantitative and qualitative findings was conducted during the interpretation stage using connecting and merging techniques. The results revealed that transformational leadership exerted by the madrasah principal had a positive and significant effect on teacher professionalism (β = 0.744; p < 0.001), with an R² value of 0.554. The qualitative findings reinforced these results by demonstrating that teacher professionalism was fostered through the principal's exemplary leadership, vision internalization, technology-based competency development, and dialogic academic supervision, all of which contributed to the establishment of a sustainable learning culture. The study concludes that transformational leadership not only enhances teacher professionalism but also creates a learning ecosystem that continuously supports teachers' professional competence development within the madrasah context.